The Complete Kubernetes Guide Become an Expert in Container Management with the Power of Kubernetes. - Baier, Jonathan (Learning path., 2019)
This Learning Path walks you through the basic and advanced features of Kubernetesand teaches you all that you need to know for easily and efficiently manage your containerized applications.